Natural Compounds Triterpene Glycosides. Part 1 and Part 2 - Azimova, Shakhnoza S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
'Natural Compounds: Plant Sources, Structure and Properties' details the properties of over 7,500 chemical compounds of pharmacological interest found in plants. Each volume systematically covers occurrence of the compounds in plants, illustrations of chemical structures plus physical-chemical, spectral, and pharmacological data. Entries are indexed by plant name, subject, and pharmacological property. This provides unique coverage of information on compounds isolated from some 3,000 plants, including many from central Asia and Russia, that are not well known elsewhere. The entries for each compound share a similar format. The entries are preceded by tabulated information on the occurrence of the compounds in plants etc. The highly experienced team of compilers from the renowned Institute of the Chemistry of Plant Substances in Tashkent have expertly assessed the international literature and include data only when confident of its validity, e.g. excluding data where measurement processes cause degradation of the original compound.
Keywords: Chemistry; Chemistry, Organic; Pharmacy; Botany; Chemistry; Organic Chemistry; Pharmacy; Plant Sciences